2007
DOI: 10.1074/jbc.c700111200
|View full text |Cite
|
Sign up to set email alerts
|

UBE1L2, a Novel E1 Enzyme Specific for Ubiquitin*

Abstract: UBE1 is known as the human ubiquitin-activating enzyme (E1), which activates ubiquitin in an ATP-dependent manner. Here, we identified a novel human ubiquitin-activating enzyme referred to as UBE1L2, which also shows specificity for ubiquitin. The UBE1L2 sequence displays a 40% identity to UBE1 and also contains an ATP-binding domain and an active site cysteine conserved among E1 family proteins. UBE1L2 forms a covalent link with ubiquitin in vitro and in vivo, which is sensitive to reducing conditions. In an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 139 publications
(135 citation statements)
references
References 27 publications
6
126
1
2
Order By: Relevance
“…These results suggest that FAT10 is exclusively activated by Uba6. Consistent with earlier studies (13)(14)(15), ubiquitin was activated by both Uba6 and UAE (data not shown).…”
Section: Uba6supporting
confidence: 81%
See 2 more Smart Citations
“…These results suggest that FAT10 is exclusively activated by Uba6. Consistent with earlier studies (13)(14)(15), ubiquitin was activated by both Uba6 and UAE (data not shown).…”
Section: Uba6supporting
confidence: 81%
“…sc-67203) and Uba6 (Millennium). 15 N-Labeled FAT10 and ubiquitin internal standards were generated by expressing FAT10 or ubiquitin pDEST14 vectors into in Rosetta/DE3 cells (EMD Biosciences, Inc., Darmstadt, Germany) supplemented with BioExpress cell growth media (U-15 N, 98%, Cambridge Isotope Laboratories, Inc., Andover, MA). Proteins were purified using HiTrap SP column and Superdex 75 column (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation and conjugation of FAT10 to its substrate proteins is performed most probably by a three step enzymatic cascade, as described for ubiquitin. The FAT10 E1 activating enzyme UBA6 acts as a bi-specific E1 enzyme, because it is able to activate both, FAT10 and ubiquitin (Chiu et al, 2007;Pelzer et al, 2007). In doing so, UBA6 is able to distinguish between the two modifiers and binds FAT10 with a higher affinity than ubiquitin, although the adenylation and transthiolation reaction is slower for FAT10 than for ubiquitin (Gavin et al, 2012).…”
Section: Which Are the Targets Of Fat10 And How Is It Conjugated To Imentioning
confidence: 99%
“…Moreover, inhibitors of the proteasome are already in use or under further investigation for the development of cancer therapies (Chen and Dou, 2010;Tu et al, 2012). Ubiquitylation as well as poly-ubiquitylation is achieved by an enzymatic cascade where first ubiquitin is adenylated at its C-terminal diglycine residue by one of its two ubiquitin E1 activating enzymes UBE1 (Ciechanover et al, 1981) or UBA6 (Jin et al, 2007;Pelzer et al, 2007) and then transferred onto the active site-cysteine of the respective E1 enzyme to form a thioester bond. In a second step, ubiquitin is transferred to the active site cysteine of a cognate ubiquitin conjugating enzyme (E2) by a transthiolation reaction.…”
Section: Introductionmentioning
confidence: 99%